Characterization of La0.5sr0.5co0.5ti 0.5o3-? as Symmetrical Electrode Material for Intermediate-Temperature Solid-Oxide Fuel Cells - Troncoso-Aguilera, L (2012)
La0.5Sr0.5Co0.5Ti0.5O 3-? perovskite oxide has been prepared as polycrystalline powder, characterized and tested as cathode and anode material for solid-oxide fuel cells. The oxidized material is suggested to present mixed ionic-electronic conductivity (MIEC) from "in-situ" neutron powder diffraction (NPD) experiments, complemented with transport measurements; the presence of a sufficiently high oxygen deficiency, with large displacement factors for oxygen atoms suggest a large lability and mobility combined with a semiconductor-like behaviour with a maximum conductivity of 29 S cm-1 at T = 850 °C. A complete reversibility towards reduction-oxidation processes has been observed, where the reduced Pm-3m perovskite with La0.5Sr 0.5Co0.5Ti0.5O2.64 composition has been obtained by topotactical oxygen removal without abrupt changes in the thermal expansion. The oxidized material shows good performance working as a cathode with LSGM electrolyte, yielding output power densities close to 500 mW/cm2 at 850 °C. At intermediate temperatures (800 °C) it may be used as a cathode or as an anode, yielding power densities of 220 and 170 mW/cm2, respectively. When used simultaneously as cathode and anode a maximum power density of 110 mW/cm2 was obtained. Therefore, we propose the La0.5Sr0.5Co0.5Ti 0.5O3-? composition as a promising candidate for symmetrical electrode in intermediate-temperature SOFC. Copyright © 2012, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.